Litter traits for gilts fed 4 or 7.4 lb feed during the first ten days after breeding - Davis, Duane L.; Zhang, Z.; Stevenson, Jeffrey S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
We tested the effects of feeding 4 or 7.4 lb of a complete gestation diet to gilts during days 0 to 2 or 3 to 10 after first detected estrus (day 0) and mating. There was a tendency (P = .11) for the 7.4 lb/day treatment to increase litter size when fed from day 0 to 2 and to decrease (P = .17) litter size when fed from day 3 to 10. Gilts artificially inseminated at puberty farrowed fewer (P < .05) pigs than gilts inseminated at a second or later estrus.
Keywords: Swine; Feeding level; Flushing; Embryo survival; Litter traits; Fertility